Drill Training Method for 6 Weeks Improves Bottom Passing Ability at Volleyball Academy KU-17 - Ainurrozi, Afif Surya; Purwoto, Septyaningrum Putri; Himawan, Agus (Universitas Negeri Surabaya, 2023)
This research aims to determine how increasing the drill training method affects the bottom passing ability at Volkas Volleyball Academy KU-17. The population used in this research was Volkas Volleyball Academy KU-17, taken using the purposive sampling method and a sample of 15 people. The test in this study was used to obtain lower passing score data during the pretest and posttest. The analysis method in this research used the paired sample t-test. The results of hypothesis testing using a paired sample t-test produce a sig value of 0.000 < 0.05 with a calculated t value of -4.878 < 2.1445, which means that H0 is rejected and Ha is accepted, it can be concluded that there is an influence of drill method training on increasing passing—bottom at Volkas Volleyball Academy KU-17. The results of this study produced data that there was an increase in lower passing at Volkas Volleyball Academy KU-17, as evidenced by the paired sample t-test sig value of 0.000 < 0.05 with a calculated t value of -4.878 < 2.1445, which means that H0 was rejected and Ha accepted. With pretest test results of 40.2 and posttest test results of 45.67. Based on the results and discussion of research that has been carried out, it is concluded that the drill training method can improve lower passing in volleyball games, especially at Volkas Volleyball Academy KU-17.